POTENSI BERBAGAI TANAMAN SEBAGAI INANG INOKULUM MIKORIZA ARBUSKULAR DAN EFEKNYA TERHADAP PERTUMBUHAN TANAMAN JAGUNG DAN KEDELAI DI TANAH ULTISOL - Doli Saputra Hasibuan; T. Sabrina; Alida Lubis (Universitas Sumatera Utara, 2014)
The objective of this research would be to examine the micorrhyze inoculum quality of severaltypes of hosts using ultisol as growing medium on maize and soybean growth. The research hasbeen conducted in greenhouse and laboratory of Biotechnology of Soil, Faculty of Agriculture,North Sumatera University. To achieve this objective, a non-factorial group random sampling hasbeen used through some treatments: J J (maize was applied with mycorrhyze inoculum of maize), DJ (maize was apolied with mycorrhyze inoculum of soybeans), S J (maize was applied withmycorrhyze inoculum of setaria grass), T J (maize was appolied with mycorrhyze inoculum ofgroundnuts), J D (soybean was applied with mycorrhyze inoculum of maize), D D (soybean wasapplied with mycorrhyze inoculum of soybeans), S D (soybean was applied with mycorrhyzeinoculum of setaria grass), T D (soybean was applied with myzoerhyze inoculum of groundnuts).The result of research indicated that application of myzorrhyze inoculum of maize, soybean,groundnut and setaria grass to maize and soybean plants has not significant effect of increassing theheight of plants, wet weight of shoot, dry weight of shoot, wet weight of root, degree of rootinfection, uptakes of N and P in plants of maize and soybean plants.Keywords: host, mycorrhyze inocolum, maize, soybean, groundnut, and setaria grass